2016
DOI: 10.1111/ajt.13782
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant CD4 Count Influences Immune Reconstitution and Risk of Infectious Complications in Human Immunodeficiency Virus–Infected Kidney Allograft Recipients

Abstract: In current practice HIV+ candidates with CD4 >200 cells/mm3 are eligible for kidney transplantation. However, the optimal pre-transplant CD4 count above this threshold remains to be defined. We evaluated clinical outcomes in patients with baseline CD4 >350 and <350 cells/mm3 among 38 anti-thymocyte globulin (ATG)-treated HIV- to HIV+ kidney transplants performed at our center between 2006 and 2013. Median follow-up was 2.6 years. Rates of acute rejection, patient and graft survival were not different between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
3
35
1
1
Order By: Relevance
“…We recently showed that ATG-treated HIV + kidney transplant recipients with a baseline CD4<350 cells/mm 3 have higher risk of severe lymphopenia (CD4<200 cells/mm 3 ) and associated infectious complications [21]. Given the narrow therapeutic window of ATG in this population, it has been proposed that administration of this agent should be restricted to patients at very high immunologic risk for rejection [5, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that ATG-treated HIV + kidney transplant recipients with a baseline CD4<350 cells/mm 3 have higher risk of severe lymphopenia (CD4<200 cells/mm 3 ) and associated infectious complications [21]. Given the narrow therapeutic window of ATG in this population, it has been proposed that administration of this agent should be restricted to patients at very high immunologic risk for rejection [5, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Given the narrow therapeutic window of ATG in this population, it has been proposed that administration of this agent should be restricted to patients at very high immunologic risk for rejection [5, 21]. Considering the null rates of acute rejection at 3 years we observed among HIV + recipients categorized to the upper CD3 + HLA-DR + tertile, it is conceivable that individuals with high pre-transplant immune activation levels, particularly those with CD4<350 cells/mm 3 , might benefit of less intense lymphodepletion during induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance IS included tacrolimus, mycophenolate mofetil, and prednisone. Additional details about IS and antimicrobial prophylaxis protocols at our center have been previously described …”
Section: Methodsmentioning
confidence: 99%
“…Outcomes assessed at 1 year post‐transplant in each group were as follows: patient survival, death‐censored graft survival, and acute rejection. We also assessed the incidence of serious infections within the first 6 months post‐transplant, defined as infections requiring admission to the intensive care unit during initial transplant hospitalization or re‐admission to the hospital after discharge …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation